Corrección de la acidez y su efecto en la fijación biológica del n y disponibilidad de nutrientes en el suelo, en la estación experimental La Argelia, Loja - Ordoñez Aguilar, Diana Maritza (2022)
Acidity or acidification is one of the greatest limitations and factors that affect soil fertility, altering its normal functioning, and in the same way affecting biological nitrogen fixation (FBN) and availability of essential macro and micronutrients in the soil, causing low productivity in crops. Based on the above, the objective of the present investigation was to determine the effect of different amendments for the correction of soil acidity on biological nitrogen fixation (FBN), the availability of nutrients in the soil and agricultural yield of beans. The study was carried out at the La Argelia Experimental Station, in the city of Loja, La Argelia neighborhood, establishing a completely randomized experimental design (DCA), with five treatments and three repetitions. The treatments used were agricultural lime, magnesium oxide, dolomite and calcium oxide plus the control. Each experimental unit constituted a plot of 10 m2. An ANAVA analysis of variance was applied with LSD Fisher comparisons (p < 0.05) in InfoStat 2019 free version statistical software. The treatment with calcium oxide presented an increase in pH of 6.92, followed by agricultural lime with 6.78, dolomite treatment with 6.39 and, finally, magnesium oxide with 6.31, respectively. Regarding the biological fixation of nitrogen, it was evidenced that the correction of acidity with calcium oxide and agricultural lime presented high values 57.5 and 51.9 % with respect to the other treatments. There was a significant effect of the acidity correction on nitrogen (N), calcium (Ca) and iron (Fe), pH between 6.4 to 6.7 (calcium oxide and agricultural lime) showed greater availability of N and Ca. At pH below 6.4 (magnesium oxide and dolomite) the availability of iron (Fe) is greater. There was no significant effect of acidity correction for phosphorus (P), potassium (K), magnesium (Mg), manganese (Mn) and copper (Cu). The values remained high in all treatments, as well as the initial value in phosphorus (P) and copper (Cu). And being mean values in all treatments as well as the initial value in manganese (Mg). For potassium (K) and magnesium (Mg), the values remained medium, as well as the initial value, at pH between 6.3 and 6.9 (agricultural lime and calcium oxide). In the agricultural yield of beans, there was no statistically significant difference between treatments, that is, there was no significant effect of acidity correction on crop yield. Keywords: acidity, BNF, availability, nutrients, yield.